Estimating dual deposit insurance premium rates and forecasting non-performing loans: Two new models - Naoyuki Yoshino; Farhad Taghizadeh-Hesary; Farhad Nili (Asian Development Bank Institute (ADBI), 2015)
Risky banks that endanger the stability of the financial system should pay higher deposit insurance premiums than healthy banks and other financial institutions that have shown good financial performance. It is necessary, therefore, to have at least a dual fair premium rate system. In this paper, we develop a model for calculating dual fair premium rates. Our definition of a fair premium rate in this paper is a rate that could cover the operational expenditures of the deposit insuring organization, provides it with sufficient funds to enable it to pay a certain percentage share of deposit amounts to depositors in case of bank default, and provides it with sufficient funds as precautionary reserves. To identify and classify healthier and more stable banks, we use credit rating methods that employ two major dimensional reduction techniques. For forecasting non-performing loans (NPLs), we develop a model that can capture both macro shocks and idiosyncratic shocks to financial institutions in a vector error correction setting. The response of NPLs/loans to macro shocks and idiosyncratic innovations shows that using a model with macro variables only is insufficient, as it is possible that under favorable economic conditions some banks show negative performance or vice versa. Our final results show that stable banks should pay lower deposit insurance premium rates.
Keywords: G28; G21; E44; 330; dual deposit insurance premium rates; non-performing loans; idiosyncratic shocks; fair premium rates